PRIVATISASI AIR BERSIH DALAM PERSPEKTIF EKONOMI ISLAM - Prasetyo, Heri (Program Studi Manajemen, 2022)
This research is motivated by the idea that water is God's creation to meet the needs of human life in the world, therefore the use of water must be based on a sense of responsibility and fully for the welfare of mankind. government policy regarding the right to cultivate water can be said to be not simple with the mandate of article 33 of the 1945 Constitution. The enactment of law number 7 of 2004 concerning water resources was followed by the issuance of a number of regional regulations (perda) related to the right to cultivate water contributed greatly to the clean water crisis. By using field research with an economic and pragmatic approach as well as an approach that is oriented towards Islamic economic values, with a normative juridical approach and an economic approach by examining law and Law No. 7 of 2004.Privatization of water is an attempt to commercially own water resources which eliminates government intervention and the function of social security, on the basis of which Islamic economics through the concept of ownership regulates that water is not an object that is perfectly owned, because there the ownership rights of everyone are attached without exception, Water resources are included in public ownership, with restrictions on the ownership of clean water, the utility of water is an oppression of human rights over water resources because it is contrary to Islamic values.